Evaluation of salivary IL-6 and carbonic anhydrase VI as biomarkers in periodontal health and disease - Asma khan; Saghir Jafri; Mohsin Ali Cheema; Abdullah Ehsan; Syeda Ayesha Fatima; Tayyaba Sheikh (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Saliva contains proteins that may serve as biomarkers for oral diseases. Periodontitis, an inflammatory gum disease linked to poor oral hygiene, alters salivary composition. This study aimed to compare salivary carbonic anhydrase VI (CA VI) and interleukin-6 (IL-6) levels among individuals with healthy gums, mild, and moderate periodontitis.METHODOLOGY: In this cross-sectional study, ELISA measured CA VI an enzyme involved in pH regulation and IL-6 a pro-inflammatory cytokine in saliva. Periodontal status was assessed via periodontal pocket depth (PPD) and clinical attachment loss (CAL) using a Michigan O probe.RESULTS: The Kruskal-Wallis test showed no significant differences in CA VI and IL-6 levels across the groups (p = 0.217 and p = 0.579, respectively). However, in healthy individuals, CA VI levels were inversely correlated with PPD (Spearman’s ρ = –0.455) and CAL (ρ = –0.433). In mild periodontitis, CA VI negatively correlated with PPD (ρ = –0.467). In moderate periodontitis, IL-6 levels showed a significant inverse correlation with CAL (Pearson’s r = –0.408).CONCLUSION: Salivary CA VI and IL-6 levels were not significantly different across periodontal health statuses, suggesting limited use as diagnostic biomarkers. Nonetheless, significant correlations between CA VI and periodontal parameters in healthy and mildly affected individuals and IL-6 and CAL in moderate periodontitis indicate potential roles in disease progression monitoring.